2016
DOI: 10.1093/aje/kwv333
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Noise Frequencies and the Incidence of Hypertension in a Retrospective Cohort Study

Abstract: Occupational noise exposure is associated with cardiovascular disease, but little is known about the contributions of noise frequency components. This retrospective study investigated the relationship between exposure to different noise frequencies and the incidence of hypertension. A cohort of 1,002 volunteers from 4 machinery and equipment manufacturing companies in Taichung, Taiwan, was followed from 1973 to 2012. Personal noise measurements and environmental octave-band analyses were performed to divide su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…Title and abstract screening, citation tracking, and the reference list search identified 180 studies for the full text screening. We included 24 studies published (in 26 publications) between 1977 and 2019 [ 44 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Despite extensive searching, we were unable to obtain the complete text of six publications through our library and excluded 148 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Title and abstract screening, citation tracking, and the reference list search identified 180 studies for the full text screening. We included 24 studies published (in 26 publications) between 1977 and 2019 [ 44 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Despite extensive searching, we were unable to obtain the complete text of six publications through our library and excluded 148 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Further, because we chose an inception cohort with the intent of limiting the healthy worker survivor effect, our mean follow‐up period was 6.5 years. Two studies that reported positive associations between noise exposure levels and hypertension may have benefitted from employment durations between 8 and 15 years …”
Section: Discussionmentioning
confidence: 99%
“…No increased risk of hypertension associated with increased noise exposure was observed among blue‐collar industrial workers, though a significant difference in risk was observed between blue‐collar and white‐collar female workers. More recently, Liu et al examined both noise level and frequency in relation to incident hypertension and found that certain frequencies were positively and linearly associated with risk of hypertension. In addition, they detected a significant relationship between higher noise exposure levels and incident hypertension; however, the relationship lost significance after adjusting for multiple comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…As a limitation of the animal experimental studies we would like to mention that specific frequency components of traffic noise exert differentially pronounced health effects in human subjects (Chang et al, 2014;Liu, Young, Yu, Bao & Chang, 2016) and, accordingly, translation of animal experimental data may be hampered by species differences in noise perception. Moreover, we have shown that white noise exposure, despite application of similar sound pressure levels and despite pres-ence of a continuous band of frequencies in white (or pink) noise, displayed no adverse cardiovascular effects in mice (Munzel et al, 2017b), suggesting that the noise pattern (e.g.…”
Section: Molecular Insights From Animal Studies On Aircraft Noise Expmentioning
confidence: 99%